Oneirotherapy in Overweight and Obesity - Sanjay Kalra; Saurabh Arora; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Oneirotherapy is a form of psychotherapy that is based on visual imagery and symbolism. In this communication. We discuss the role of oneirotherapy, or using vivid imagery, as adjuvant therapy in obesity care. Oneirotherapy can be used to promote acceptance of, and adherence to, prescribed therapy. It may also help improve quality of life and enhance self-esteem. However, oneirotherapy alone, without following a healthy lifestyle and or taking antiobesity medication, will help manage weight only in one’s dreams Keywords: Holistic care, mind body medicine, personcentric care, psychosocial aspects